Retinal structural changes and aging in Parkinson’s disease: Evidence from the Persian cohort study - Farzaneh Nikparast; Zohreh Ganji; Nooshin Akbari-Sharak; Ali Shoeibi; Naser Shoeibi; Hoda Zare (Photodiagnosis and Photodynamic Therapy, 2025)
Background: Parkinson’s disease (PD) affects not only the brain but also the retina. Due to its anatomical and developmental similarities to the brain, the retina may serve as a non-invasive biomarker for the detection and monitoring of PD. This study aimed to investigate retinal structural changes and laboratory data in PD. Method: A total of 125 patients with PD and 972 healthy controls from the PERSIAN Organizational Cohort Study were included in the analysis of macular and peripapillary OCT parameters, as well as laboratory test results. Group comparisons were performed using independent samples t-tests or Mann–Whitney U tests. The associations between OCT measurements and age were evaluated using Pearson’s correlation coefficient or Spearman’s rank correlation. Results: Significant thinning of the perifoveal region was observed in PD patients, particularly in the superior (p = 0.042) and nasal (p = 0.021) quadrants and the superior hemisphere (p = 0.017) of the left eye, and in the temporal quadrant (p = 0.028) of the right eye. Additionally, optic disc area (p = 0.009) and focal loss volume (p < 0.001) were increased. Age-related reductions in Average pRNFL (p < 0.001) and GCC (p = 0.001) thickness were more pronounced in the PD group. Conclusion: The significant reduction in perifoveal thickness and volume, along with a notable increase in optic nerve-related OCT parameters, may serve as potential biomarkers for the diagnosis of PD. pRNFL, GCC, and perifoveal retinal thickness demonstrated a strong association with age in patients with PD.